Surface Morphology And Electrical Properties Of Copper-Nickel Alloy Thin Film Deposited On Printed Circuit Board Using Thermal Evaporation Method - Yusop, Nurul Khalidah (2017)
The increased in input/output (I/O) density due to the demand of high performances in devices caused the routing density on printed circuit board increased. This caused the board size increases due to the increased of trace width and trace spacing. Apart from that, the consumers preferred a small devices. This definitely against the customer’s need because increasing in width trace caused the size of package also increases. One way to overcome this is by replacing the passive resistor with the thin film resistor. Therefore in this study CuNi thin film was selected as a thin film resistor material. The experiments consists of 3 parts (1) to measure the thickness of the thin film with desired resistance (2) to determine the Cu content with the desired electrical properties (3) to build the prototypes of the thin film resistor into suitable size as used by the industry and simulate the design to obtain a high value of insertion loss and low value of return loss. All samples were deposited using thermal evaporator at constant pressure. The adhesion between the film and the substrate were observed by using peel off test. The morphology were observed using SEM while the composition of the phase of the samples were confirmed using XRF, EDX and XRD. It was found out that 70 nm is the minimum thickness that suitable for thin film resistor. The quality of thin film resistors depends on Cu contents. 80/20 wt.% CuNi was found to be the desired composition with the best electrical properties compared to others. The same compositions was used for simulation purpose. From the simulation it can be said that all the thin film resistor are able to perform in frequency up to 5GHz. 80/20 wt.% CuNi able to achieved -2 dB for insertion loss and -30 dB for return loss.